2016
DOI: 10.3748/wjg.v22.i27.6268
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and safety of endoscopic submucosal dissection for lower rectal tumors with hemorrhoids

Abstract: ESD on lower rectal lesions with hemorrhoids could be performed safely, similarly to that on rectal lesions extending to the dentate line without hemorrhoids. In addition, all hemorrhoids after ESD improved to various degrees, depending on the resection range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 20 publications
5
25
0
Order By: Relevance
“…This agent is used in upper gastrointestinal endoscopy to suppress the pharyngeal reflex. The effectiveness of lidocaine during ESD was recently reported . First, a local injection of lidocaine was used for pain relief when a rectal lesion extending to the dentate line was treated by ESD .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This agent is used in upper gastrointestinal endoscopy to suppress the pharyngeal reflex. The effectiveness of lidocaine during ESD was recently reported . First, a local injection of lidocaine was used for pain relief when a rectal lesion extending to the dentate line was treated by ESD .…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of lidocaine during ESD was recently reported . First, a local injection of lidocaine was used for pain relief when a rectal lesion extending to the dentate line was treated by ESD . In another study, it was reported that submucosal injection of local anesthetic during gastric ESD reduced post‐ESD pain .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations